PENINGKATAN KESADARAN MASYARAKAT DALAM MENUNAIKAN ZAKAT UNTUK PEMBERDAYAAN EKONOMI MASYARAKAT - Wahida Z (Sekolah Tinggi Ilmu Syariah (STIS) Al-Aziziyah Sabang, 2022)
Raising public awareness in paying zakat is very urgent. This can be done by internally increasing the religiosity of the community through the preaching of the scholars about zakat. And the external side, by increasing accountability and transparency in zakat management, and increasing government participation in socializing regulations on zakat, as well as providing accreditation to zakat, zakat management and sanctions for institutions that violate. Keywords: Awareness, Da'wah, Socialization and Zakat